1988
DOI: 10.3354/meps049127
|View full text |Cite
|
Sign up to set email alerts
|

Pico- and ultraplankton Sargasso Sea communities: variability and comparative distributions of Synechococcus spp. and algae

Abstract: Ultraplankton (0.2 to 5 ~m ) provided >88% of euphotic layer chlorophyll (Chl) at 2 Sargasso Sea stations in July/August 1986. Communities were further characterized to quantify the separate abundances of phycoerythrin-fluorescing cyanobacteria Synechococcus spp. and Chl-fluorescing algae in 0.2 to 0 6, 0.6 to 1 and 1 to 5 pm size fractions. Throughout the water-column at both stations, the majority of Synechococcus cells were consistently found in the 0.6 to 1 pm fraction; the Sargasso Sea WH7803 serogroup wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 34 publications
2
45
0
Order By: Relevance
“…Indeed, such an increase in the ratio of PE:cell with depth has been observed in field populations of Synechococcus spp. in the North Atlantic (Glover et al 1988) using a non-extractive method of PE estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, such an increase in the ratio of PE:cell with depth has been observed in field populations of Synechococcus spp. in the North Atlantic (Glover et al 1988) using a non-extractive method of PE estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Cell concentrations are generally in the range of 10 5 to 10 8 I" 1 for prokaryotic forms and 10 5 to 10 7 I" 1 for eukaryotic forms (Joint 1986). Phycoerythrin-rich prokaryotic forms appear to dominate in oligotrophic oceanic regions (Murphy & Haugen 1985;Joint 1986;Glover et al 1988). In more nutrient-rich coastal waters the composition of the population is generally more variable (Glover et al 1988) with a significant contribution by eukaryotic forms (Hall & Vincent 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Phycoerythrin-rich prokaryotic forms appear to dominate in oligotrophic oceanic regions (Murphy & Haugen 1985;Joint 1986;Glover et al 1988). In more nutrient-rich coastal waters the composition of the population is generally more variable (Glover et al 1988) with a significant contribution by eukaryotic forms (Hall & Vincent 1990). The picoplankton community may also be structured vertically with an increased abundance of eukaryotic forms sometimes occurring with increasing depth (e.g., Glover, Smith & Shapiro 1985;Murphy & Haugen 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Landry et al 1984, Campbell & Carpenter 1986a, b, Iturriaga & Mitchell 1986, Iturnaga & Marra 1988, Weisse 1988, Kudoh et al 1990, Caron et al 1991, Kuosa 1991, Sherr et al 1991, Pick & Berube 1992. Furthermore, using a sensitive chemiluminescence method for NO,-analysis, Glover et al (1988a, b) found that introduction of ca 10 nM NO3-(below the detection Limit of the conventional colorimetric method) to surface waters in the stratified Sargasso Sea was followed by a Synechococcus spp.…”
Section: Introductionmentioning
confidence: 99%